STRATEGI KONVERGENSI MEDIA RRI SEMARANG DALAM MEMPERTAHANKAN EKSISTENSI RRI SEMARANG DI ERA DIGITAL - Faizal Maghriza, Mukhammad; Sunarto, Sunarto; Hasfi, Nurul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Media convergence is interpreted as the combination of various information and communication technology services, along with increasing digitalization making it possible for people to access various types of media content, making media organizations produce content that can be enjoyed across media. On the other hand, internet users continue to increase and people's attention to conventional media, especially radio, has decreased, which has caused the radio industry to begin to decline. A strategy is needed for radio to still be heard, namely by carrying out media convergence. This research aims to find out how the media convergence process strategy is carried out by Radio Republik Indonesia Semarang to maintain its existence in the digital era. The theory used in this research is Media Convergence Theory, while the method used is qualitative research using a case study approach, by conducting interviews and observations in the RRI Semarang environment who are involved and related to the process of implementing media convergence. The results of this research indicate that RRI Semarang views media convergence as quite important in its position as a Public Broadcasting Institution and reference media which needs to anticipate changes in information consumption patterns in society. This is done through various owned platforms such as RRI Digital, the RRI.co.id page, the RRI NET channel, social media for each program and news, as well as the YouTube channel. Planning is carried out in the broadcast and news sector, guided by the LPP RRI Broadcast Guidelines Book and the Reporting Style Book. The technical convergence strategy refers to understanding the direction of convergence, positioning as a media verifier, following the flow of convergence, strengthening the technical and multimedia sectors, adapting content, and building interactivity. The promotional strategy refers to the use of soft-selling through promotions on personal accounts and hard-selling through on-air and off-air promotions. This has implications for analytical and quality achievements, although it still has shortcomings.